Country-specific life satisfaction effects of unemployment: Does labour market policy matter? - Melike Wulfgramm (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2012)
Public policy shapes the lives of individuals, and even more so if they depend on state support. But to what extent can well-being differences between individuals living in different European states be traced back to the specific national public policy designs? This paper tests the intervening effects of the design and generosity of labour market policy on the life satisfaction of the unemployed. To estimate cross-level interaction effects in random intercept models, macro-indicators on active labour market policy spending and unemployment benefit generosity of 21 European countries are merged with survey data from the European Social Survey (ESS). While unemployment has strong negative life satisfaction effects all over Europe, the generosity of passive labour market policy moderates this effect to a surprisingly large extent: The adverse effect of unemployment is almost doubled in a country with meagre unemployment benefits. This moderating effect can be explained both by a resource as well as a non-pecuniary mechanism. In contrast, the moderating effect of active labour market policy is less robust across model specifications. – – Das Leben aller Bürger wird durch die Ausgestaltung des Wohlfahrtsstaats gerahmt und dies gilt in besonderem Maße für diejenigen, die auf Unterstützung durch den Sozialstaat angewiesen sind. Doch inwiefern lassen sich die Unterschiede im subjektiven Wohlbefinden von europäischen Arbeitslosen durch die nationale Ausgestaltung der Arbeitsmarktpolitik erklären? Dieses Paper untersucht den moderierenden Einfluss der Generosität und des Designs aktiver und passiver Arbeitsmarktpolitik auf die Lebenszufriedenheit der betroffenen Arbeitslosen. Hierzu werden die Umfragedaten von 4 Wellen des European Social Surveys gemeinsam mit arbeitsmarkpolitischen Makrodaten in einer Mehrebenenanalyse untersucht. Während sich der negative Lebenszufriedenheitseffekt von Arbeitslosigkeit in allen Ländern bestätigt, zeigt sich ein überraschend starker moderierender Effekt der Generosität der Arbeitslosenunterstützung: Der nachteilige Effekt von Arbeitslosigkeit verdoppelt sich in Ländern mit eingeschränkten Leistungen im Vergleich zu großzügigeren Ländern beinahe. Hierbei finden sich Hinweise auf nichtpekuniäre sowie Ressourcenmechanismen. Der positive moderierende Effekt der aktiven Arbeitsmarktpolitik stellt sich hingegen als deutlich weniger robust dar.
Keywords: 300; labor market policy; welfare state; unemployment; life satisfaction; subjective well-being; unemployment benefits